Breeding oats for subtropical environments - Federizzi, Luiz Carlos (MTT, 2004)
In subtropical environments, Farmers are able to grow two crops per year in the same land, usually under no till system. The two grow season are spring/summer, when farmers cultivated soybean or corn (the cash crops), and winter/spring, when farmers cultivate small grains. Subtropical environments are characterized by a great variation of climatic parameters during the oat growing season (winter/spring), especially over years. Old oat cultivars (released before 1980) had plant cycles as long as 180 days, hindering the cultivation of a summer crop. Selection for genes for photoperiod insensibility reduced the plant cycle to 125-130 days in the earlier genotypes. Under subtropical conditions, North American oat genotypes (photoperiod sensitive) flower in late spring, when the Brazilian adapted oats are ready or almost ready to harvest. The change in life cycle was possible by conscious crossing and selection of genotypes insensitive to photoperiod. Genetics studies revealed two mechanisms controlling flowering date in oats: 1) temperature dependent; 2) photoperiod dependent (Locatelli, et al. 2002). Plant stature was also reduced from 150-160 cm to 90-120 cm using minor effect genes for plant height. Visual selection of early plant vigour helped to increased harvest index, allowing to increase grain yield at same time that stature was reduced. Test weight was increased from 30-40 kg/100 l to 50-55. Milling yield increased from about 40% to 62%. The most important diseases are crown and stem rust, followed by leaf spots. Resistance to crown rust is based in major effect genes, which have short duration under cultivation conditions. Therefore, oat breeding programs need to release resistant varieties almost every year. Partial resistance has been studied. Strong selection for broad adaptation to subtropical environments permitted the farmers to obtain grain yields greater than 3 t/ha consistently over the years. Locatelli, A.B. et al. 2002. 22ª Reunião da Comissão Brasileira de Pesquisa de Aveia, p. 391-393.
Keywords: Ka; adaptation; selection; flowering date; plant height; grain yield